The vocabulary richness of children's television in Ireland: A cross-generational comparison. - Mc Tiernan, Kathleen (My University, 2018)
This research investigates whether the vocabulary richness of children’s programming has changed over one generation, and therefore compares the programmes offered in 1992 to those offered in 2017. Three hours of programming were sourced, transcribed and coded using the Computerised Language Analysis (CLAN) software (MacWhinney, 1984). CLAN is a language analysis software originally developed for the purpose of analysing child language which allows for the detailed transcription and analysis of linguistic data, including statistical measures of lexical diversity (Pye & MacWhinney, 1994). The total words, words per minute, vocabulary diversity, total object, action, attribute and affective-state words as well as the total object, action, attribute and affective-state words spoken in the presence of a referent were calculated and compared for the programming. The vocabulary richness of children’s television has decreased over time. The number of words spoken in the presence of referents in the programming has increased over time, with this increase being significant for action and attribute words. This pattern of findings reflects a trend in children’s television towards the production of programmes of reduced lexical complexity which may facilitate children’s word learning.
PUBLISHED
Keywords: Vocabulary; Language acquisition; Media and Television; Input; Identities in Transformation; CHILD LANGUAGE; Irish Linguistics; Psycholinguistics; Children; Communication; Education